Environmental Fate of Toxic Volatile Organics from Oil Spills in the Niger Delta Region, Nigeria - Nimisingha Sanchez Deinkuro; Charles William Knapp; Morufu Olalekan Raimi; Nanlok Henry Nimlang (Three E Science Institute, 2021)
Over the years, the environmental degradation of ecological resources from crude oil pollution and its human health impacts is receiving more global attention. The utilization of environmental models capable of predicting the fate, transport, and toxicity of chemicals in spilt crude oil can provide essential knowledge required to deal with the complexity associated with the fate of volatile petroleum chemicals in the environment. This paper explores the environmental fate of toxic volatile organics from an oil spill in the Niger Delta Region of Nigeria. Results from the literature implicated sabotage and operational failures from pipelines as primary causes of crude oil spillages. The generation of a fugacity model using EPI Suite™ revealed that Koc values greatly influence the behavior of BTN. Benzene, Toluene, and Naphthalene (BTN) were partitioned into three compartments based on organic-carbon partitioning coefficient (Koc). The organic-carbon partitioning coefficient (Koc) was computed as a function of soil-water distribution coefficient (Kd) and percentage organic matter (%OM). Koc was used to determining the possible risk posed on delicate ecological resources. Aquatic toxicology estimation using Ecological Structural Activity Relationship revealed that all chemicals were not toxic even at over-estimated Koc values. This research established the usefulness of screening level environmental modeling tools in assessing ecological risk and hence helpful in developing site-specific models for monitoring chemicals in the environment, which can assist governments, policymakers, and industries in designing appropriate regional disaster management plans.